2021
DOI: 10.1016/s2665-9913(21)00104-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-steroidal anti-inflammatory drug use and outcomes of COVID-19 in the ISARIC Clinical Characterisation Protocol UK cohort: a matched, prospective cohort study

Abstract: Background Early in the pandemic it was suggested that pre-existing use of non-steroidal anti-inflammatory drugs (NSAIDs) could lead to increased disease severity in patients with COVID-19. NSAIDs are an important analgesic, particularly in those with rheumatological disease, and are widely available to the general public without prescription. Evidence from community studies, administrative data, and small studies of hospitalised patients suggest NSAIDs are not associated with poorer COVID-19 outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 32 publications
2
58
0
Order By: Relevance
“…Ten papers described death in NSAID users [ 12 , 14 , 17 24 ], with various exposure periods, including current or acute exposure [ 12 , 14 , 25 ], or within 30 days [ 17 ] or 4 months [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten papers described death in NSAID users [ 12 , 14 , 17 24 ], with various exposure periods, including current or acute exposure [ 12 , 14 , 25 ], or within 30 days [ 17 ] or 4 months [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four papers studied death in ibuprofen users, for current exposures [ 14 , 24 ], exposures of < 7 days [ 26 ] or exposures of < 4 months, in rheumatoid arthritis, or in the general population [ 23 ] (Table 2 d). The paper by Wong et al, in either the general population or the rheumatoid arthritis population, was considered as two different studies [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians may be reluctant to use NSAIDs, including relatively selective COX-2 inhibitors, due to the known risk of cardiovascular events (33) and the hepatotoxicity of nimesulide, which is admittedly very low when the drug is prescribed at the recommended daily dose and time of administration (34). On the other hand, in a large cohort of over 4200 patients admitted to the hospital who had taken NSAIDs within the 2 weeks preceding hospital admission, the use of these drugs was not associated with higher mortality or increased severity of COVID-19, as compared to a matched group of NSAID non-users (35). Moreover, another study provided no indication that harm was induced by NSAIDs, as demonstrated by the lack of increased risk of poorer outcomes in COVID-19 patients given NSAIDs compared with those treated with paracetamol, or NSAID non-users (36).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a recent large prospective, multicentre cohort study based on the ISARIC Clinical Characterisation Protocol UK dataset (>78,000 patients) failed to identify an association between pre-existing NSAID use (within two weeks before hospitalization) with higher in-hospital mortality or worse outcome (critical care admission, need for invasive ventilation, need for oxygen, and acute kidney injury) in hospitalized COVID-19 patients. In a subgroup analysis, ibuprofen use was not associated with an increased risk of mortality compared to other NSAIDs or no NSAIDs ( Drake et al, 2021 ). Similarly, an Israeli retrospective cohort study reported that the use of ibuprofen before SARS-CoV-2 infection was not associated to increased mortality or the need for respiratory support (oxygen administration and mechanical ventilation) compared to non-NSAID users or acetaminophen users ( Rinott et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%